2013
DOI: 10.1007/s00467-013-2419-6
|View full text |Cite
|
Sign up to set email alerts
|

The quality of cardiovascular disease care for adolescents with kidney disease: a Midwest Pediatric Nephrology Consortium study

Abstract: Background Cardiovascular disease is the leading cause of increased mortality for adolescents with advanced kidney disease. The quality of preventive cardiovascular care may impact long-term outcomes for these patients. Methods We reviewed records of 196 consecutive adolescents from 8 centers with pre-dialysis chronic kidney disease, on dialysis, or with a kidney transplant who transferred to adult-focused providers. We compared cardiovascular risk assessment and therapy within and across centers. Predictors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Our recent study of pediatric maintenance hemodialysis patients demonstrated that only one-third had received an echocardiogram, the gold standard for diagnosis of cardiac disease [13]. Another recent study evaluated cardiovascular risk assessment in pediatric chronic kidney disease, dialysis, and kidney transplant patients at the time of transition to adult nephrology care [14]. Only 58% of cardiovascular risk factor assessments were documented, including echocardiogram, smoking assessment, family history of cardiovascular disease, lipid profile, and physical activity assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study of pediatric maintenance hemodialysis patients demonstrated that only one-third had received an echocardiogram, the gold standard for diagnosis of cardiac disease [13]. Another recent study evaluated cardiovascular risk assessment in pediatric chronic kidney disease, dialysis, and kidney transplant patients at the time of transition to adult nephrology care [14]. Only 58% of cardiovascular risk factor assessments were documented, including echocardiogram, smoking assessment, family history of cardiovascular disease, lipid profile, and physical activity assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this is the first study to compare self-reported physical activity and screen time in adolescents with CKD to that of healthy peers. Prior studies have shown that pediatric patients who progress to ESKD have a significantly higher overall mortality that the general population as well as a particularly increased cardiovascular mortality [3, 710]. Studies in adult patients with CKD suggest that physical activity is a strong predictor of cardiovascular mortality, and studies in both pediatric and adult ESKD patients suggest that physical activity may be a modifiable risk factor for cardiovascular disease [1323, 3641].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a significant concern in this population, both for the higher rates of cardiovascular mortality as compared to healthy peers as well as the increased risk of premature death in early adulthood due to CVD [1–11]. Overall mortality for children who progress to ESKD is 30 to 150 times higher than that of the general population and cardiovascular mortality is 1000 times higher [3, 710]. CVD is the leading cause of mortality in adult ESKD patients with a fourfold risk of death as compared to populations without ESKD [1, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Among those with kidney transplants, more proactive preventive care may reduce the high risk of future cardiovascular mortality observed in early adulthood. 4 Among those in the general population, similar strategies that encourage cardiovascular health behaviors are likely to be important for longer term gains in survival. 5 For all children and adolescents, additional increases in longer term survival will likely require more system-wide approaches to cardiovascular risk management.…”
mentioning
confidence: 99%
“…5 For all children and adolescents, additional increases in longer term survival will likely require more system-wide approaches to cardiovascular risk management. [4][5][6] How will additional improvements in allograft survival be achieved? Although primary nonfunction and delayed graft function declined substantially over time, 2 it is not clear whether these decreases mediated the corresponding increases in death-censored graft survival.…”
mentioning
confidence: 99%